SENYUM DAN TAWA NABI SULAIMAN DI LEMBAH SEMUT: TELAAH KRITIS ATAS KISAH NABI SULAIMAN DALAM AL-QUR’AN - Aris Fauzan (TASHWIR, 2022)
Abstract: Smiling and laughter are psycho-physical activities that occur in human beings and primates. Laughter is native to every human being, even primates. Theories of laughter and humor originated in ancient times with the view that laughter is an expression of feelings of superiority over another person. Theories of laughter and humor date back to ancient times, holding that laughter is an expression of feelings of superiority over others. Nietzsche's view that laughter is the appropriate response to the ultimate liberation of an individual. This confirms that anyone who laughs is actually free, because honest laughter is a spontaneous expression of the soul and is not bound by any rules. While Samuel Johnson wrote: Men have been wise in many different modes, but they have always laughed the same way. In terms of laughter, they have the same way.Keywords: Smiling; Laughter; Expression of the Soul. Abstrak: Senyum dan tawa merupakan aktivitas psiko-fisik yang terjadi pada makhluk jenis manusia dan primata. Tawa itu merupakan asli setiap manusia, bahkan primata. Theories of laughter and humor originated in ancient times with the view that laughter is an expression of feelings of superiority over another person. Teori tawa dan humor berasal dari zaman kuno berpandangan bahwa tawa adalah ekspresi perasaan superioritas atas orang lain. Nietzsche's view that laughter is the appropriate response to the ultimate liberation of an individual,tertawa itu menggambarkan puncak kebebasan seorang individu. Ini menegaskan siapa pun orang yang tertawa sejatinya dirinya terbebas, karena tertawa yang jujur itu merupakan ekspresi jiwa yang spontan dan tidak terikat oleh aturan apapun. Sementara Samuel Johnson, menuliskan: Men have been wise in many different modes, but they have always laughed the same way,dalam kearifan manusia memiliki banyak cara yang berbeda, tetapi dalam soal tertawa mereka memiliki cara yang sama. Kata Kunci: Senyum; Tawa; Ekspresi Jiwa.